The Effect of the Board’s Human and Social Capital on Firm Performance: A Comparative Institutional Analysis - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2012)
This study aims at investigating how institutional logics influence the efficacy of a board’s human and social capital to enhance performance measures across different institutional contexts. We theorize that human capital is more influential in a context categorized as individualistic while social capital is more effective in a collectivistic context. In addition, we expect human capital to be more closely linked with the monitoring function of boards while social capital may rather be used to address resource provision needs. We test our assumptions in a comparative study encompassing the U.S., Germany, and Singapore. Preliminary results for the effect of board network ties (social capital) and various measures of human capital (diversity of directors’ functional background, educational level, tenure) largely support our predictions.